Manifesto for a wide-range theory of dramaturgy - Szatkowski, Janek (Peripeti, 2025)
Manifesto for a wide-range theory of dramaturgy is an introduction to an experiment: It argues for a need to make a distinction between dramaturgy as a reflection theory inside the art system and dramaturgy as a scientific theory inside the science system. Grand-theory as universalizing and subsuming practice has been tested and failed, mid-range theories have been inspirational in cultural theory studies, and so, the manifesto argues the need for a theory of wide-range as a starting point for a re-description and construction of a new theory for dramaturgy. The experiment uses an operative and radical systems-theory and combines communication theory with a theory of evolution (poiesis) and of society as hyper-complex with functionally differentiated systems.